2010
DOI: 10.1128/mcb.00469-10
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Peptide Deformylase Disrupts Mitochondrial Function

Abstract: Deformylases are metalloproteases in bacteria, plants, and humans that remove the N-formyl-methionine off peptides in vitro. The human homolog of peptide deformylase (HsPDF) resides in the mitochondria, along with its putative formylated substrates; however, the cellular function of HsPDF remains elusive. Here we report on the function of HsPDF in mitochondrial translation and oxidative phosphorylation complex biogenesis. Functional HsPDF appears to be necessary for the accumulation of mitochondrial DNA-encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
2
40
1
Order By: Relevance
“…In some cases, these proliferation defects were attributed to dysfunctional mitochondrial respiration (Escobar-Alvarez et al, 2010;Skrtić et al, 2011). However, this interpretation is at odds with data from a vast scientific literature that demonstrate that glycolysis fuels the metabolic demands of cellular proliferation (reviewed by Hanahan and Weinberg, 2011).…”
Section: Box 1 Mitochondrial Protein Synthesiscontrasting
confidence: 42%
See 2 more Smart Citations
“…In some cases, these proliferation defects were attributed to dysfunctional mitochondrial respiration (Escobar-Alvarez et al, 2010;Skrtić et al, 2011). However, this interpretation is at odds with data from a vast scientific literature that demonstrate that glycolysis fuels the metabolic demands of cellular proliferation (reviewed by Hanahan and Weinberg, 2011).…”
Section: Box 1 Mitochondrial Protein Synthesiscontrasting
confidence: 42%
“…The proliferation of cultured mammalian cells can be impaired following disruption of mitochondrial function Escobar-Alvarez et al, 2010;Richter et al, 2010;Richter et al, 2013;Rorbach et al, 2008;Skrtić et al, 2011;Soleimanpour-Lichaei et al, 2007;Uchiumi et al, 2010). In some cases, these proliferation defects were attributed to dysfunctional mitochondrial respiration (Escobar-Alvarez et al, 2010;Skrtić et al, 2011).…”
Section: Box 1 Mitochondrial Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and pharmacological studies revealed that inhibition of NME activity in vivo leads to the destabilization of several central proteins of either plastid or mitochondrial proteomes Bouzaidi-Tiali et al, 2007;Moon et al, 2008;Escobar-Alvarez et al, 2010). Moreover, organellar NME inhibition induces a cascade of events that impair the biogenesis of the entire compartment as well as the development of the whole organism.…”
Section: Introductionmentioning
confidence: 99%
“…12 The PDF inhibitors may induce a tumor-specific mitochondrial membrane depolarization and ATP depletion, which promote cell death or arrest proliferation in a wide variety of cancer cell lines. [5][6][7] However, the exact mechanism of anticancer effect of PDF inhibitors is still unclear.…”
mentioning
confidence: 99%